2023
DOI: 10.3389/fenrg.2023.1149446
|View full text |Cite
|
Sign up to set email alerts
|

High entropy nanomaterials for energy storage and catalysis applications

Abstract: In the past decade, high entropy alloys have been a research field of interest largely attributed to the enormous possibilities in alloy compositions, solid solution microstructures, and enhanced properties. The progress accomplished so far in the innovative growth and development of the mechanical, nanomechanical, chemical, electrochemical properties for energy storage systems using high entropy alloys on the nanoscale has limited reports in the literature. Mastering the synthesis of high entropy alloys is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 120 publications
0
4
0
Order By: Relevance
“…Downsizing HEAs to the nanoscale provides additional application possibilities resulting from the high surface‐to‐volume ratio and quantum confinement effect, making them suitable for catalysis [12–15] energy storage, [16,17] magnetic, [18–20] and biomedical applications [21,22] . Feng et al [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Downsizing HEAs to the nanoscale provides additional application possibilities resulting from the high surface‐to‐volume ratio and quantum confinement effect, making them suitable for catalysis [12–15] energy storage, [16,17] magnetic, [18–20] and biomedical applications [21,22] . Feng et al [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Laser ablation synthesis, known for its precision and minimal contamination risk, has high energy requirements and is prone to producing inconsistent particle sizes. The above challenges need to be addressed to make HEA nanomaterial synthesis more viable for widespread industrial applications [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of noble metal and noble metal-based oxide catalysts (such as Pt, RuO 2 , and IrO 2 ), along with traditional alloy catalysts (like Fe-Pt, Pt-Ni, CuPdAu), in large-scale applications is hindered by their high costs, limited natural resources, and scarcity [8]. This creates a strong incentive to innovate and fabricate electrocatalysts that are cost-effective, exceptionally efficient, and easily accessible, surpassing the catalytic performance of noble metals and conventional alloys, hence the importance of HEAs in catalytic applications such as the hydrogen evolution reaction (HER), oxygen reduction reaction (ORR), oxygen evolution reaction (OER), CO 2 reduction reaction (CO 2 RR), and ammonia (NH 3 ) decomposition [9]. In their study on the synthesis of Co CuFeNi particles by hydrogen reduction-assisted ultrasonic spray pyrolysis (USP-HR), Küçükelyas and his co-workers found that these particles exhibited high ferromagnetic behavior, making them promising materials for catalytic applications [10].…”
Section: Introductionmentioning
confidence: 99%